Control of a Battery Supported Dynamic Voltage Restore - Ramachandaramurthy, V.K.; Fitzer, C.; Arulampalam, A.; Zhan, C.; Barnes, M.; Jenkins, N. (IEE Proceedings on Generation Transmission and Distribution, 2002)
Control of a Dynamic Voltage Restorer (DVR) based on Space Vector PWM is described. The control algorithm is able to compensate for any type of voltage sag and uses a software phase-locked loop to track phase jumps during a fault. The control algorithm restores the depressed voltages to the same phase and magnitude as the nominal pre-sag voltages and then gradually tracks to the phase of the depressed voltages. Experimental results are shown to validate the control algorithm using a 3-phase prototype with a power rating of 10kVA.